Geometry of tidal inlet systems: A key factor for the net sediment transport in tidal inlets. Issue 10 (21st October 2014) - Ridderinkhof, W.; de Swart, H. E.; van der Vegt, M.; Alebregtse, N. C.; Hoekstra, P.
Abstract The net transport of sediment between the back‐barrier basin and the sea is an important process for determining the stability of tidal inlet systems. Earlier studies showed that in a short basin, tidal flats favor peak ebb‐currents stronger than peak flood currents, implying export of coarse sediment, while shallow basins favor stronger flood currents. The new elements considered in this study are (1) arbitrary basin lengths, (2) a narrow inlet that connects the basin to the sea, (3) an asymmetric tidal forcing, and (4) radiation damping. The objective is to gain fundamental insight in how the geometry of a tidal inlet system affects the net sand transport in a tidal inlet. For this purpose, a width‐averaged and depth‐averaged analytical model was constructed. It is found that the length of a back‐barrier basin controls the effect that nonlinear hydrodynamic processes have on the tidal asymmetry, and consequently controls whether the currents in the inlet are flood‐dominant or ebb‐dominant. Furthermore, the cross‐sectional area of the inlet controls the ratio between the net sediment transports that results from tidal asymmetry and that caused by the interaction of the principal tide with the residual current. Finally, it is shown that the effect of an asymmetric tidal forcing on the net sand transport depends on the length of the back‐barrier basin with respect to the tidal wavelength in that basin.